Marketing Mix Strategy Analysis Using 4p Concept (Price, Product, Place, Promotion) At Wery Bakery In Gunungsitoli - Hulu, Kristina Variastina; Laia, Otanius; Waruwu, Suka'aro (UNIVED Press, 2026)
This study aims to Analyze Marketing Mix Strategy Using the 4P Concept (Price, Product, Place, Promotion) at Wery Bakery in Gunungsitoli, and which Marketing Mix Strategy using the 4P concept is the advantage of Wery Bakery. The research method used is qualitative, with an in-depth approach to social and human phenomena. This study found that the Marketing mix strategy currently implemented is to have a variety of products and maximize promotions through social media, provide various prices and create consumer comfort in shopping at Wery Bakery and this has been running but is not optimal. The Marketing Mix Strategy using the 4P concept which is the advantage of Wery Bakery includes Product quality, as well as varying prices and being able to compete and exist in the midst of much competition, Wery Bakery is advised to always develop its marketing strategy again properly and maintain product quality, and conduct continuous evaluations to adjust the strategy with the feedback received. Implementation of the right marketing mix strategy can help Wery Bakery increase consumer loyalty and be able to maintain its competitiveness in the market.